Identifying the anti-inflammatory response to lipid lowering therapy. A position paper from the working group on Atherosclerosis and vascular biology of the European society of cardiology - Tunon, J; Badimon, L; Bochaton-Piallat, M; Carioua, B; Daemen, M; Egido, J; Evans, P; Hoefer, I; Ketelhuth, D; Lutgens, E; Matter, C; Monaco, C; et al. (Oxford University Press, 2018)
Dysregulated lipid metabolism induces an inflammatory and immune response leading to atherosclerosis. Conversely, inflammation may alter lipid metabolism. Recent treatment strategies in secondary prevention of atherosclerosis support beneficial effects of both anti-inflammatory and lipid-lowering therapies beyond current targets. There is a controversy about the possibility that anti-inflammatory effects of lipid-lowering therapy may be either independent or not of a decrease in low-density lipoprotein cholesterol. In this Position Paper, we critically interpret and integrate the results obtained in both experimental and clinical studies on antiinflammatory actions of lipid-lowering therapy and the mechanisms involved. We highlight that: (1)Besides decreasing cholesterol through different mechanisms, most lipid-lowering therapies share anti-inflammatory and immunomodulatory properties, and the anti-inflammatory response to lipid-lowering may be relevant to predict the effect of treatment, (2)Using surrogates for both lipid metabolism and inflammation as biomarkers or vascular inflammation imaging in future studies may contribute to a better understanding of the relative importance of different mechanisms of action, and (3)Comparative studies of further lipid lowering, antiinflammation and a combination of both are crucial to identify effects that are specific or shared for each treatment strategy.